Immunomodulatory and antiarthritic activities of Smilax zeylanica - P Veeresh Babu; T Ashwini; M. Vamsi Krishna; M. Ganga Raju (International Journal of Phytomedicine, 2017)
Smilax zeylanica Linn has been traditionally used in the treatment of rheumatoid arthritis but, no scientific data has been published supporting the claimed ethanomedical use. This study was designed to investigate the immunomodulatory and antiarthritic activities of Smilax zeylanica. Methanolic extract of Smilax zeylanica (MESZ) roots was tested for its immunomodulatory activity by NBT reduction test. Antiarthritic activity of the same was tested by in vitro protein denaturation and in vivo complete Freunds adjuvant (CFA) induced arthritis. MESZ showed its significant effect on both cell mediated and humoral immunity to suppress stimulated immune responses in NBT reduction test . It also markedly inhibited protein denaturation in in vitro model. Extract at 200 mg/kg and 400 mg/kg showed statistically significant inhibition ( p<0.05) of the edema formation in CFA model. Histopathological studies of ankle joints also supported this finding. The presence of steroids in the extract might be responsible for the prominent immunomodulatory and antiarthritic activities of the plant. Hence the present study concluded that Smilax zeylanica holds immunomodulatory and antiarthritic activities.